Communication—Electrodeposition, Microstructure and Magnetic Properties of Co2FeSn Heusler Alloy Nanowires. Issue 16 (1st January 2018) - Lu, Hongxia; Liu, Yuchan; Kou, Xinli
Abstract : Co2 FeSn Heusler alloy nanowires with the diameters of 30 nm and 60 nm were firstly prepared by direct current electrodeposition. Magnetic measurements revealed the excellent soft ferromagnetism of Co2 FeSn nanowires. The easy magnetization axis is perpendicular to the long axis of nanowires and the magnetic reversal of Co2 FeSn nanowires occurs via coherent rotation model. In addition, the influence of the wire diameter on the magnetic properties of Co2 FeSn nanowires was discussed. Co2 FeSn Heusler alloy nanowires synthesized in this work shows tunable magnetic properties and are of potential interest for magnetic device and spintronic applications.